1997
DOI: 10.1046/j.1570-7458.1997.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hosts, temperature and food sources on the longevity of Trichogramma platneri

Abstract: Feeding experiments were conducted with Trichogramma platneri Nagarkatti (Hymenoptera: Trichogrammatidae) reared from the Angoumois grain moth, Sitotroga cerealella (Oliver) (Lepidoptera: Gelechiidae). T. platneri provisioned with host eggs do not live any longer than T. platneri without host eggs. Longevity of T. platneri is inversely related to temperature declining from 53 days at 10 °C to 3 days at 35 °C for honey‐fed parasitoids and from 9 days at 10 °C to 1 day at 35 °C for unfed parasitoids. Sugar sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 12 publications
7
58
0
2
Order By: Relevance
“…Many studies have shown that parasitoids supplied with carbohydrate-rich foods such as honey, sugar, honeydew, nectar etc., lived longer than adults that were either starved or given only water (Wäckers, 1996;McDougall & Mills, 1997;Wäckers et al, 1998;Schmäle et al, 2001). The importance of adult nutrition for V. canescens was first suggested by Beling (1932), when she observed newly emerged wasps leaving the habitat and host environment soon after emergence, and that the "returning" wasps had nectar droplets on their mouthparts.…”
Section: Effect Of Feedingmentioning
confidence: 99%
“…Many studies have shown that parasitoids supplied with carbohydrate-rich foods such as honey, sugar, honeydew, nectar etc., lived longer than adults that were either starved or given only water (Wäckers, 1996;McDougall & Mills, 1997;Wäckers et al, 1998;Schmäle et al, 2001). The importance of adult nutrition for V. canescens was first suggested by Beling (1932), when she observed newly emerged wasps leaving the habitat and host environment soon after emergence, and that the "returning" wasps had nectar droplets on their mouthparts.…”
Section: Effect Of Feedingmentioning
confidence: 99%
“…It is thus important to consider how to conserve and utilize C. vestalis in agricultural systems for successful IPM programs. 20,29 . The techniques of artificial food supply for biocontrol agents currently consist of two methods.…”
Section: Introductionmentioning
confidence: 99%
“…Species selection is based on laboratory and field trials to study the parasitoid behavior, host preference and tolerance to climate (Pratissoli et al, 2004). However, biotic and abiotic factors, including mating and feeding, might affect these biological characteristics which could influence their efficiency (Berti and Marcano, 1991;Mcdougall and Mills, 1997;Thomson and Hoffmann, 2002). Nectar and pollen are food source for Trichogramma adult in the field (Andow and Rish, 1987;Wellinga and Wysoki, 1989) and they affect their longevity and fecundity (Berti and Marcano, 1991;Mcdougall and Mills, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, biotic and abiotic factors, including mating and feeding, might affect these biological characteristics which could influence their efficiency (Berti and Marcano, 1991;Mcdougall and Mills, 1997;Thomson and Hoffmann, 2002). Nectar and pollen are food source for Trichogramma adult in the field (Andow and Rish, 1987;Wellinga and Wysoki, 1989) and they affect their longevity and fecundity (Berti and Marcano, 1991;Mcdougall and Mills, 1997). These effects are important to select the best species or even strains for biological control program since the control effectiveness might vary between the strains of the same species.…”
Section: Introductionmentioning
confidence: 99%